Drinking water quality assessment based on index values incorporating WHO guidelines and Bangladesh standards. (February 2023) - Rahman, M. Moklesur; Haque, Tasfimul; Mahmud, Azhar; Al Amin, Md; Hossain, Md Sahadat; Hasan, Md Yeasir; Shaibur, Molla Rahman; Hossain, Sabbir; Hossain, Md Alamgir; Bai, Ling
Abstract: Drinking water quality is one of the most severe concerns around the globe. This study aimed to assess drinking water quality for a densely populated region, the Jashore University of Science and Technology (JUST), and the surrounding villages. Fifty samples, including some filtered and boiled groundwater samples, were collected. The widely used arithmetic algorithm, the water quality index (WQI), was used to categorize the groundwater quality as per World Health Organization (WHO) guidelines and Bangladesh (BD) standards. Here, the WQI for all samples was calculated based on the concentrations of seventeen parameters (pH, TDS, TH, Ca 2+, Na +, Mg 2+, Cl −, SO4 2−, HNO3 −, K, PO4 3−, EC, As, Zn, Mn, Cr, and Fe). The result showed that the water quality varies laterally as well as on the sampling conditions. The calculated WQI values ranged from 16.66 to 253.50 and the average value was 91.9 for the BD standards, whereas the WHO guidelines showed WQI values between 16.74 and 605.0 with an average value of 146.90. Based on the WQI values, water samples were divided into excellent, good, poor, very poor, and unfit categories which varied from BD standards to WHO guidelines for drinking purposes. 14%, 54%, 26%, and 6% of samples fell into excellent, good, poor, and inferior categories respectively as BD standards, while these values were 38%, 22%, 14%, and 14% as WHO guidelines. The result showed that deep tube-wells (>170 ft) and shallow tube-wells (<170 ft) provide mostly good and bad quality drinking water, respectively. Highlights: Shallow aquifers in south-western Bangladesh are highly arsenic contaminated. Fifty groundwater samples were analyzed in this study. 17 physico-chemical parameters were used to estimate the water quality index value. As per WHO guidelines and Bangladesh standards, 50% and 68% of the samples were good to excellent. Shallow hand tube-well water was mostly poor to very poor in quality.